SPEECH ACTS AND DISCOURSE ANALYSIS. : SPEECH ACTS AND DISCOURSE ANALYSIS. - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
We may often come across the conception of speech act and discourse analysis in academic life. Actually. It is very important to be aware of this theory. One of the most revolutionary ideas in the development of linguistics as a discipline has been the departure from a purely linguistic approach towards a pragmatic and functional study of language. The emphasis of the Speech Act Theory is on the “act” or the function of a linguistic expression and not the grapheme, phoneme, morpheme or lexeme. It suggests a departure from linguistic analysis based on words and sentences and their semantic meaning to the meaning of “utterances” that originates from the function they fulfil, the purpose they serve or the intention with which they are used.